Malaysia Economic Monitor, December 2018 : Realizing Human Potential - World Bank Group (World Bank, Kuala Lumpur, 2018)
The Malaysia Economic Monitor consists of two parts. Part 1 presents a review of recent economic developments and a macroeconomic outlook. Part 2 focuses on a selected special topic that is key to Malaysia’s medium-term development prospects. In this edition, the focus of the special topic is on realizing human potential.